Twinning as a risk factor for neonatal acute intestinal diseases: a case-control study - Peila, C.; Spada, E.; Riboldi, L.; Capitanio, M.; Pellegrino, F.; Coscia, A. (Frontiers in Pediatrics, 2023)
Introduction Acute intestinal diseases (AID), including necrotizing enterocolitis and spontaneous intestinal perforation, are a group of conditions that typically present in preterm infants, and are associated with an elevated mortality and morbidity rate. The risk factors for these diseases remain largely unknown. The aim of the study is to identify the correlation between twinning and the development of AID. Methods A single-center retrospective case–control study was conducted. We recruited all infants with a diagnosis of AID, confirmed by anatomopathology, recovered in NICU between 2010 and 2020. Considering the rarity of the outcome, 4 matched controls for each subject were randomly chosen from the overall population of newborns. Odds Ratio (OR) and 95% Confidence Interval (CI) were calculated using a conditional logistic regression model and a multivariate model by the creation of a Directed Acyclic Graph (www.dagitty.net). Results The study population resulted in 65 cases and 260 controls. The two groups present similar median gestational age and mean birthweight in grams. The cases have a higher frequency of neonatal pathology (defined as at least one of patent ductus arteriosus, early or late sepsis, severe respiratory distress) (84.6% vs. 51.9%), medically assisted procreation (33.8% vs. 18.8%) and periventricular leukomalacia (10.8% vs. 2.7%), and a lower frequency of steroids prophylaxis (67.7% vs. 86.9%). About 50% of cases needed surgery. The OR for the direct effect were difference from one using logistic regression booth without and with repeated measures statements: from 1.14 to 4.21 (p = .019) and from 1.16 to 4.29 (p = .016), respectively. Conclusions Our study suggests that twinning may be a risk factor for the development of AID. Due to the small number of cases observed, further studies on larger populations are needed.